A generic approach to environmental assessment of microbial bioprocesses through life cycle assessment (LCA) - Harding, Kevin (University of Cape Town, 2014)
Includes abstract. === Includes bibliographical references. === The intrinsic environmental advantages of industrial scale bioprocesses over chemical processes remain a discussion point owing to limited objective analysis. Studies to date are often limited to energy or global warming considerations with little regard for full Life Cycle Assessment (LCA) analyses. This, in part, may be owing to the difficulty in obtaining the material and energy balance inventory required for such assessment at an early stage in process development. However, these studies are important in designing and selecting environmentally beneficial processes for the conversion of renewable resources to commodity and energy products. The overall objective of the thesis is to obtain the data required to perform these LCA analyses. To achieve the overall objective, the thesis presents a methodology to obtain the material and energy balance data estimates required for the LCA of industrial bioprocesses through a generic flowsheet model. The flowsheet was presented as a MS-Excel spreadsheet allowing aerobic or anaerobic production of intra- or extracellular products using batch or continuous microbial processes. A database presented in the model facilitates the use of a variety of carbon, nitrogen, sulphur and phosphorus inputs and provides relevant constants and physical data. Typically downstream processing units were taken into account and included downstream chemical inputs (reacting or inert). The model was built using a stoichiometric approach, first principles and rules of thumb.